The Reflection of IT Governance on the Organizational Performance of the IT Center and its Associated Units - Tikrit University - Suhaib Abdel Rahman Tuhma Al-Doory (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Information technology (IT) is considered one of the basic requirements for organizations due to its closeness to the concept of electronic management. Therefore, governance is an effective part in the field of IT within the current orientation of organizations, noting that the goal of this governance is reflected in ensuring oversight and achieving control within the framework of a strategy that suits the organization’s goals, managing risks and resources, and delivering value at the appropriate time with the aim of raising the level of the organization’s performance. This has increased interest in this field in a way that has given it a character of importance and at the same time enabling organizations to strive to provide the best practices to their clients. From there, the study has found an entry point to describe a case in (Tikrit University / Information Technology Center and its associated units in the colleges) by selecting a random sample with a total size of (68) respondents. A number of (55) answers are obtained from them, relying on the descriptive analytical approach and using the SpssV23 program. This situation was evident in the statement of the relationship and the impact it has on the reflection of information technology governance on organizational performance. The study has detected that there are significant correlations and influence between information technology governance and the organizational performance of the information technology center and its units at a rate of (63.5%). This indicates the effective contributions to crystallizing the cognitive framework for information technology governance, including the implementation of work mechanisms, laws, and instructions, including their basic concepts, while adopting an appropriate strategy linked to all risk indicators and required resources, and delivering value in a timely manner. This in turn is reflected in the reality of the information technology center’s performance by increasing the improvement rates in organizational performance that has increased significantly, reaching the latest levels of excellence in service provision.